Influence of Pre-sowing Magnetic treatment on the germination and growth of (Abelmoschus esculentus) seeds - Vaidya, R. D.; Patel, Kaushik R.; Bokha, Dipak (Vidyapith (વિદ્યાપીઠ), 2015)
An attempt has been made to study the effect of magnetic field on germination rate and growth of Okra (Abelmoschus esculentus) seeds. The genetically uniform dry seeds were exposed to magnetic field induced by an electromagnet. The seeds were exposed to 50 mT, 100 mT and 200 mT magnetic field for 5, 10 and 30 minute period. The seeds with no magnetic field treatment were considered as control. Both treated and non-treated seeds were sown in similar conditions. Growth parameters like germination rate, root length, stem height and numbers of secondary roots were observed. The results showed that magnetism has a significant positive effect on plant growth. Plant seeds under the influence of the magnetic field had a higher germination rate and relative growth of observed parameters compare to the control. No adverse effects of magnetism on plant growth were noticed.